Moving from evidence to action: prioritisation of pediatric injury issues for focused injury prevention programming. (1st March 2011) - Charyk-Stewart, T; Polgar, D; Parry, N; Girotti, M J
Abstract : Objective: To develop a prioritised, evidence-informed list of pediatric injury issues to be addressed through injury prevention initiatives. Method: A quantitative review of trauma data with qualitative stakeholder discussions. Data representing all levels of severity from ED visits to deaths were reviewed and ranked by age (<1, 1–4 years, 5–9 years, 10–14 years, 15–17 years). Specific topics for each of the top issues (MVC, recreational, falls, intentional, drowning and other) were discussed based on qualitative criteria (ie, effectiveness, opportunity gaps) and individually scored on a 5-point Likert scale. The sum of these scores was ranked. This qualitative rank was added with the quantitative rank from the data to determine the overall ranking, with the lowest rank sum as the top priority. Results: Shaken baby syndrome (SBS) was ranked as the top priority. The top five ranking injury issues are presented in Table 1 . Conclusion: With competing demands and limited resources, this method utilises data and stakeholder input to decide where to focus efforts. It allowed us to move from evidence to action, by implementing and evaluating new programs including SBS-prevention and unsafe driving programs.